Statistical Analysis of Food Safety Sampling Data at Home and Abroad - LI He-li; LI Li; ZHAO Cheng-ming; HAN Shi-he (Liang you shipin ke-ji)
Some countries or regions have taken measures to ensure food safety, such as food safety sampling monitoring plan. This paper focuses on the statistical analysis of domestic and foreign food safety sampling inspection data. It begins with an introduction to the laws and regulations, institutions, and characteristics of food safety sampling inspection reports in the United States, the European Union, Japan, Canada, and China. Then the analysis and discussion are carried out, and the similarities and differences of the countries or regions in the aspects of legal system improvement, risk assessment, analysis, and the content and form of the report are pointed out. Finally, it provides conclusions and suggestions, including scientific analysis of sampling inspection results, strengthening-departmental information exchange, and increasing the transparency of regulatory information, to provide the reference for food safety regulatory decision-making.